Pengaruh Harga dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan di PT JNE Kudus - Riezky Army Riesha (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine whether the service quality provided by PT JNE Kudus at the established price significantly affects customer loyalty. The research adopts a quantitative approach, employing Structural Equation Modeling (SEM) analysis on data collected from 165 respondents through questionnaires. The findings reveal that both price and service quality provided by PT JNE Kudus significantly influence customer loyalty. These findings offer valuable insights for the company to enhance marketing strategies and customer service to maintain and grow their customer base